The mental health and labor market effects of anticipating job loss - Kai R. Miele (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2024)
Exploiting future exposure to job termination in the UK, this paper finds that sharply increased job loss expectations before job termination significantly increase mental distress. This anticipation effect is largest in tight labor markets but does not spill over within couples. In contrast, anticipating job termination allows workers to switch positions without suffering unemployment. Leveraging variation in the industry-specific labor market tightness before the job termination, this paper shows that switching from a terminated position before its closure offsets over 70 percent of the negative labor market effects of the job termination, and mitigates its entire mental burden.
urn:nbn:de:hbz:465-20240708-093213-1
Keywords: D84; I18; J28; J63; 330; Job loss; anticipation; mental health; unemployment